SYNTHESIS AND STRUCTURE CHARACTERIZATION OF (TRITOLYLSTANNYLTHIO)(TRIPHENYLSTANNYL)METHYL TRIPHENYLSTANNANECARBODITHIOATE (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2015)
The title compound Ph3SnCS2CH(SSnTol3)SnPh3 has been isolated as major product after the attempted alkylation of lithium triphenylstannanecarbodithioate by tri(p-tolyl)tin chloride in THF as solvent and characterized by NMR spectroscopy and elemental analysis. The pink crystals of this compound have been grown from pentane/dichloromethane solution. The solid state structure has been established by X-ray crystallography analysis.
Keywords: organotin; thiocarbonyl; crystal structure; triphenylstannanecarbodithioate